Migration to Scottish New Towns and the impact on premature mortality in Glasgow: longitudinal analysis of linked Scottish Mental Survey 1947 and NHS Central Register data - Forrest, Lynne; Dibben, Chris (International Journal of Population Data Science, 2019)
Background Life expectancy in Glasgow is lower than other Scottish cities and comparable English cities. One explanation for this excess mortality is selective migration, specifically policy from the late 1940s onwards to move younger, more skilled workers and their families from Glasgow to five Scottish New Towns, established between 1948 and 1966, leaving behind those who are more deprived and unhealthy. Aim To examine the impact of migration to New Towns on premature mortality in Glasgow using linked Scottish Mental Survey 1947 and NHS Central Register data. Methods This is a new data linkage using historical data for health board moves dating back to 1948. The Scottish Mental Survey 1947 encompasses a cohort born in 1936 that had cognitive ability assessed at age 11. This cohort were of young working age at the time of New Towns policy. The cohort has been linked to NHS Central Register data, which contains information on current and previous health board location dating back to the late 1940s, as well as date of death. A time-appropriate move to the relevant health board area is used as a proxy for New Town migration. We can put people “back” to their starting geography to see what impact this has on premature mortality in Glasgow. We will examine factors associated with geographical mobility. Logistic regression and cox regression models will be used to analyse the association between migration status and early mortality. Results Preliminary results suggest that, as hypothesised, those who have migrated out of Glasgow to new Towns have lower likelihood of premature mortality than those who remain. Analysis is ongoing and we will present our final findings. Conclusion With New Towns being re-considered as an answer to the current acute UK housing shortage, it is useful to understand the, perhaps unexpected, consequences of such policies.